Complexos metálicos de fluorquinolonas: síntese, atividade biológica e estudos do mecanismo de ação - Ligiane Rios Gouvea (2013)
In this work, three Au(III) complexes of the fluoroquinolones norfloxacin (NOR), levofloxacin (LEVO) and sparfloxacin (SPAR) were prepared and characterized with physicochemical and spectroscopic techniques: [AuCl2(NOR)]Cl.2H2O (1), [AuCl2(LEVO)]Cl.2H2O (2), [AuCl2(SPAR)]Cl.2H2O (3). In these complexes, NOR, LEVO andSPAR act as bidentate neutral ligands bound to Au(III) through the nitrogen atoms of the piperazine ring, which is an unusual mode of coordination for this class of compounds. Two chloride ions occupy the remaining coordination sites. The cytotoxic activity of the fluoroquinolones and their Au(III) complexes was tested against the A20 (murine lymphoma), B16-F10 (murine melanoma) and K562 (human myeloidleukemia) tumor cell lines as well as the L919 (murine lung fibroblasts) and MCR-5 (human lung fibroblasts) normal cells lines. All complexes were more active than their corresponding free ligands. Complex [AuCl2(LEVO)]Cl (2) was selected for DNA fragmentation and cell cycleanalysis. Spectroscopic titration with calf-thymus DNA (CT DNA) showed that the complexes can bind to CT DNA, probably by an external contact (electrostatic or groove binding, resulting from stacking of the base pairs in the double helix). The complexes exhibit good binding propensity tobovine serum albumin (BSA) having relatively high binding constant values. Zn(II) complexes with norfloxacin (NOR), ofloxacin (OFLO) and sparfloxacin (SPAR) in the absence or in the presence of the 1,10-phenanthroline (phen) were obtained and characterized.In all complexes, the ligands were coordinated through oxygen atoms of the carbonyl group of the ketone and carboxylic acid. Tetrahedral geometries were proposed for [ZnCl2(NOR)].H2O (4), [ZnCl2(OFLO)] (5), [ZnCl2(SPAR)] (6) and octahedral geometry for [ZnCl2(NOR)(phen)].2H2O (8). The ionization constants of Zn(II) complexes with the NOR were calculated as the biological activity of the drug depends on its pH value. The interaction of these compounds with CT DNA suggests that the Zn(II) complexes can bind moderately by intercalation between DNAbases. The interactions between the Zn(II) complexes with the NOR and bovine serum albumin (BSA) were investigated by steady-state and time-resolved fluorescence spectroscopy at pH 7.4. The experimental data showed static quenching of BSA fluorescence, indicating that bothcomplexes bind to BSA. A modified Stern-Volmer plot for the quenching by complex (8) demonstrated preferential binding near one of the two tryptophan residues of BSA. The binding constants obtained (Kb) showed that BSA had higher affinity for complex (8) than for complex(4). This preferential interaction with protein sites could be important to their biological mechanisms of action. The analysis in vitro of the Zn(II) complexes and corresponding ligand were assayed against Trypanosoma cruzi, the causative agent of Chagas disease and the data showed that complex (8) was the most active against bloodstream trypomastigotes. Antifungal and antibacterial activities of the Zn(II) complexes were evaluated and compared with the reference drugs SPAR, OFLO and NOR. The Zn(II) complexes showed higherantimicrobial activity than the fluoroquinolones against Aspergillus niger and Salmonella typhi. Mn(II) complexes, [MnCl2(NOR)(H2O)2] (9), [MnCl2(SPAR)(H2O)2].3H2O (10), [MnCl2(NOR)(phen)].2H2O (11) e [MnCl2(SPAR)(phen)].3H2O (12), with norfloxacin (NOR)and sparfloxacin (SPAR) were obtained from MnCl2.4H2O. In all cases the NOR and SPAR coordinate in the neutral zwitterionic form to Mn(II).Complexes (912), together with the corresponding ligands were evaluated for their antifungal and antibacterial effects. Some Mn(II) complexes exhibited higher potency than the free ligants. These complexes interacted with human serum albumin by the static process. The values obtained for the thermodynamic parameters (G, H and S) suggested that the formation process of HSA-Mn(II) complexes was spontaneous and that the London forces and hydrogen bonding played important roles in stabilizing the complexes.